Improved Measurement of Extracellular Enzymatic Activities in Subsurface Sediments Using Competitive Desorption Treatment - Hoarfrost, Adrienne; Snider, Rachel; Arnosti, Carol (Frontiers in Earth Science, 2017)
Extracellular enzymatic activities initiate microbially-driven heterotrophic carbon cycling in subsurface sediments. While measurement of hydrolytic activities in sediments is fundamental to our understanding of carbon cycling, these measurements are often technically difficult due to sorption of organic substrates to the sediment matrix. Most methods that measure hydrolysis of organic substrates in sediments rely on recovery of a fluorophore or fluorescently-labeled target substrate from a sediment incubation. The tendency for substrates to sorb to sediments results in lower recovery of an added substrate, and can result in data that are unusable or difficult to interpret. We developed a treatment using competitive desorption of a fluorescently-labeled, high molecular weight organic substrate that improves recovery of the labeled substrate from sediment subsamples. Competitive desorption treatment improved recovery of the fluorescent substrate by a median of 66%, expanded the range of sediments for which activity measurements could be made, and was effective in sediments from a broad range of geochemical contexts. More reliable measurements of hydrolytic activities in sediments will yield usable and more easily interpretable data from a wider range of sedimentary environments, enabling better understanding of microbially-catalyzed carbon cycling in subsurface environments.